1979
DOI: 10.2307/3897836
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Mule Deer and Cattle on Big Sagebrush Range in British Columbia

Abstract: Interaction between deer and cattle took various forms. The potential for direct competition was greatest in spring. Both deer and cattle selected bluebunch wheatgrass and crested wheatgrass while Sandbergs bluegrass was most often used by deer. Evidence of indirect interaction was observed. Moderate or heavy fall grazing by cattle made the spring forage more attractive to deer by removing mature forage. Light grazing did not exert any appreciable effect on deer distribution. The spring range of mule deer in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…For example, in Oregon, BLM administers 33% of mule deer winter range including >50% of our study area. Land management activities, including livestock grazing (Robinette et al , Willms et al ), timber harvest (Bergman et al , Bombaci and Pejchar ), energy development (Johnson et al , Sawyer et al ), and recreational activities (Wisdom et al , Stankowich ) could affect mule deer distributions and population dynamics. Additionally, industrial and residential development on or near public lands is increasing, resulting in reduced winter range area and increased disturbance to deer (Sawyer et al , Kline et al , Duncan and Burcsu ).…”
mentioning
confidence: 99%
“…For example, in Oregon, BLM administers 33% of mule deer winter range including >50% of our study area. Land management activities, including livestock grazing (Robinette et al , Willms et al ), timber harvest (Bergman et al , Bombaci and Pejchar ), energy development (Johnson et al , Sawyer et al ), and recreational activities (Wisdom et al , Stankowich ) could affect mule deer distributions and population dynamics. Additionally, industrial and residential development on or near public lands is increasing, resulting in reduced winter range area and increased disturbance to deer (Sawyer et al , Kline et al , Duncan and Burcsu ).…”
mentioning
confidence: 99%
“…In turn, grazing by elk and mule deer in spring is unlikely to compete with cattle use in summer-fall, provided that elk or mule deer grazing is not excessive (Hobbs et al 1996a(Hobbs et al , 1996bBrewer 2002). We recommend that resource managers focus their forage utilization and range trend monitoring efforts in foothill sagebrush grasslands, particularly on southerly aspects, as these are preferred sites for spring grazing by elk, mule deer, and cattle (Hudson et al 1976;Willms et al 1979;Nelson and Leege 1982).…”
Section: Management Implicationsmentioning
confidence: 99%
“…This overlap can be beneficial to wild ungulates, for example, when elk or mule deer preferentially select feeding sites where previous cattle grazing has improved forage palatability (Willms et al 1979;Grover and Thompson 1986;Jourdonnais and Bedunah 1990;Frisina 1992;Yeo et al 1993;Crane 2002). However, elk and mule deer will avoid or not select sites previously grazed by cattle if cattle utilization is excessive and extant (Hudson et al 1976;Crane 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslandsare not usually considered cover areas, but Nellis' has found that giant wildrye stands are used as fawn-rearing cover in Idaho. Grasslands adjacent to cover may provide valuable forage, depending on the interactions of stand size, grazing management, and season (Roll et al 1979;Leckenby 1978c;Reynolds 1962Reynolds ,1964Tueller and Monroe 1975;Willms et al 1979). …”
Section: Non-shrub Communities Grasslands In Generalmentioning
confidence: 99%
“…Because grazing and burning affect the phenology of forage plants, appropriate management can prolong the availability of high quality forage for mule deer (Anderson and Scherzinger 1975;Leckenby 1968Leckenby , 1978cTueller and Tower 1979;Willms et al 1979Willms et al , 1980. Sheehy (1978) found that during the rearing period, fawns usually stayed within 1 kilometer (0.6 mi) of the fawning site.…”
mentioning
confidence: 99%